PERANCANGAN SISTEM KERJA REPLENISHMENT HPL YANG ERGONOMIS DI WAREHOUSE PT XYZ - Syafrudiansyah Ichwal; Florida Butarbutar; Syarif Hadiwijaya (INDUSTRIKRISNA, 2026)
The condition of the work system that is less ergonomic can cause a non-ideal posture, so that workers get tired easily because there are several parts of the body that receive static loads continuously, therefore the existing work system needs to be improved. The purpose of this study is to determine the impact of worker complaints, determine posture while working, and design an ergonomic work system that can provide convenience to operators when doing their work. This research method uses Nordic Body Map (NBM) to analyze worker complaints, Rapid Entire Body Assessment (REBA) and Ovako Working Analysis System (OWAS) to measure body posture, and anthropometric data to determine the dimensions of the trolly replenishment design. Data was obtained from the collection of data on worker complaints before design, posture before design, anthropometric data, and cycle time data. By designing a new work system based on three main aspects, namely layout, movement, and work aids, significant changes were made to complaints, work posture, and operator cycle time. Among them are the 5 biggest complaints of workers before the design, namely the waist (23), back (22), left shoulder (18), right shoulder (19), and right upper arm (18), after the design of the 5 complaints decreased significantly to waist (9), back (8), left shoulder (9), right shoulder (9), and right upper arm (9). Then the REBA score before the design, which is (9), is included in the high risk, after the design is analyzed with OWAS into category (1), meaning that there is no musculoskeletal system problem in this attitude. And the cycle time that originally took 43.4 minutes to work on 1 HPL crate, became 37.0 minutes.